The Reproduction of the Weddell Seal Leptonychotes weddellii (Phosidae) in the Waters of the Argentine Islands Archipelago - P. B. Khoyetskyy (Ukrainian Antarctic Journal, 2018)
Objective. The study of Leptonychotes weddellii (Phocidae) reproduction in the waters of the Argentine Islands archipelago. Methods. The inventory of Weddell seals was carried out on the islands of the archipelago by the route method with an inspection of the places where seals are likely to be located. Moving to the islands, depending on the ice situation, the weather conditions, was carried out on the sea ice or using a boat. The identification of L. weddellii was carried out in accordance with common methods. Results. In September—October 2015, in the waters of the Argentine Islands archipelago, five breeding sites of L. weddellii were revealed. At the first site (the Three Little Pigs Islands), five parturition cases were identified, at the second one (near the old English station), the births of 4 seal pups were recorded, at the third one (the Forge Islands) — 4 pups, at the fourth one (the Black — Leopard Islands) — 8 pups, and at the fifth breeding site (Grotto — Corner — Uruguay Islands) — 11 seal pups. The sixth site was probably the Barchans Islands. During the period of the study, over 76 % of the female seals with offspring and about 24 % without seal pups were recorded. Observations indicate that females swim in advance into the water of the archipelago for further reproduction. It was found that in six females parturitions occurred a day after their appearance on the island’s shore or the ice cover, some females brought pups four, six and seven days later. During September – October 2015 more than 50 % of females gave birth to pups on the ice cover, but at the distance which did not exceed 10—15 m from the shore. The births of pups at a considerable distance from the shores of the island were recorded rarely. Conclusions. In the spring of 2015, the first female seal at birth was recorded in early September, the last one — in the second ten-day period of October, the maximum number of parturition cases was found in the third ten-day period of September. The breeding period lasted 38 days. There were recorded 32 female seals that gave birth to 18 male pups and 14 female pups. The number of seal pups was higher than in previous years, there was no postnatal mortality and no mortality of young animals was recorded. Our studies provide an opportunity to estimate the size and structure of the species population in the waters of the Argentine Islands archipelago. However, some issues of Weddell seals biology in the period of breeding need further study, in particular: spatial-temporal distribution, emigration and immigration processes in the area of the archipelago, which are related to the ice situation, the availability of feed and  reproduction.